DIAGNOSTIC CRTITERIA OF ORTHODONTIC TREATMENT WITH EXTRACTION OF SOME TEETH - О.М. Makarova (Проблеми екології та медицини)
Orthodontic treatment for adults is always difficult process, which requires morphological, functional, aesthetic factors and limited possibilities of dentoalveolar teeth positioning. One of the most actual issues of orthodontic correction in adults is teeth extractions by orthodontic. Nowadays, when there is a concept of «arch development», skeletal enlargement and miniimplants, treatment with extraction should be correctly explained and determined by orthodontic treatment and should not be caused to functional status and face aesthetics, which provides qualitative and stabile result of treatment. Besides, necessity of teeth extraction of some teeth which are written in medical protocol, secures a doctor from law risks. The aim of the investigation was to establish correlative link between parameters of morphometric analysis of control and diagnostic models of jaws by Snagina and roentgenologic parameters of lateral cephalometry by Kim. Adult patients aged from 18 to 32 years old (50) by the 1st class of dentofacial abnormalities and the degree of teeth crowding were involved in the investigation. Results. Indications to treatment with teeth extraction by skeletal and dentoalveolar parameters are different, although there is connection between skeletal parameters and the width of apical basis of maxilla. Skeletal and dentoalveolar morphometric parameters that are used for evaluation of extraction necessity of some teeth and planning for orthodontic treatment is always individual. Done correlation analysis determined that single parameter of apical basis that correlates with CF is its width on the maxilla. CF has direct correlative connection of midline (r=0.52) with width of apical basis. Skeletal diagnosis and facial aesthetics is leading factor in modern orthodontics. During treatment plan one should orient into aesthetic and functional prognosis, structure of facial skeleton, and after that dentoalveolar parameters.